Validation of the FEW16 questionnaire for the assessment of physical well‐being in patients with heart failure with reduced ejection fraction: results from the CIBIS‐ELD study. (20th July 2015) - Tahirović, E.; Lashki, D. J.; Trippel, T. D.; Tscholl, V.; Fritschka, M.; Musial‐Bright, L.; Busjahn, A.; Kolip, P.; Störk, S.; Rauchfuß, M.; Inkrot, S.; Lainscak, M.; et al.
Abstract: Aims: Patients with heart failure (HF) commonly suffer from severe impairment of quality of life (QoL). One main goal of HF treatment is improvement of QoL. Physical well‐being is an essential component of QoL. To enable assessment of physical well‐being in HF patients, we validated the FEW16 questionnaire in a prospective study with patients from the Cardiac Insufficiency Bisoprolol Study in ELDerly. Methods and results: In 127 HF patients (age 73 ± 5.5 years, 72% male, 60% New York Heart Association class II, left ventricular ejection fraction 37 ± 8.5%), we measured physical well‐being (FEW16), QoL [36‐Item Short‐Form Health Survey (SF36)], and depressive symptoms [PRIME MD Patient Health Questionnaire German short version for depression (PHQ‐D)] at baseline and two follow‐up visits, and correlated FEW16 scores with QoL data and clinical parameters. FEW16 mean scores are 3.04 ± 1.04 at baseline, 3.19 ± 0.94 after 3 months, and 2.77 ± 0.94 after 2–4 years. We assessed data quality, scale assumptions, and construct validity and reliability. Cronbach's alpha for subscales resilience: 0.84; ability to enjoy: 0.80; vitality: 0.88; inner peace: 0.87; total score: 0.95. Intraclass correlation coefficient (ICC) is 0.87 (95% CI 0.84–0.89, ICC (1.4). Pearson's correlations of FEW16 with SF36 and PHQ‐D were significant. Six minutes walking distance and heart rate correlated significantly with the FEW16 total score. Conclusions: The FEW16 showed good reliability, internal consistency, and intraclass correlation. FEW16 scores correlated well with psychological and physical well‐being (SF36) and clinical markers of exercise tolerance (6 min walk test and heart rate). Our results indicate a strong correlation of self‐reported physical well‐being with psychological factors. FEW16 values at baseline predicted the development of several aspects of QoL during beta‐blocker up‐titration.